PERFORMANCE ANALYSIS OF DISEN BASED ON STUDENT PERCEPTIONS - Situmorang, Fienni Maranatha; Manurung, Melisa Feodora Quon; Silalahi, Mastiur Verawaty; Situmorang, Masni Veronika (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2026)
This study aims to analyze lecturers’ performance based on students’ perceptions in the English Education Study Program at Universitas HKBP Nommensen Pematangsiantar by adapting five service quality dimensions (SERVQUAL), namely reliability, assurance, responsiveness, empathy, and tangibles. A quantitative approach with a survey design was employed, involving 42 students selected from those who had attended courses taught by the lecturers under evaluation; data were collected using a closed-ended questionnaire with a five-point Likert scale consisting of lecturer performance items mapped onto the five SERVQUAL dimensions. The data were analyzed descriptively by calculating the mean and percentage for each dimension, which were then converted into the Respondent Achievement Level (RAL) and the Customer/Student Satisfaction Index (CSI) to describe students’ performance achievement and satisfaction levels for each dimension.